2014
DOI: 10.1111/jomf.12128
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Family System Trajectories From Pregnancy to Child's First Year

Abstract: Family systems reorganize during transitional periods, such as the birth of a new child. Longitudinal research, however, on family dynamics during the transition to parenthood is lacking. Accordingly, the authors aimed to identify family system trajectories from pregnancy to the child's first birthday and to examine their contextual predictors. Both parents (N = 702) reported autonomy and intimacy in marital (wife‐to‐husband, husband‐to‐wife) and parenting (mother‐to‐child, father‐to‐child) relations during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 41 publications
3
31
0
6
Order By: Relevance
“…Both the children and parents in these families reported high attachment security, and the children also exhibited low avoidance. The results concur with research empirically confirming the emergence of the classic family systems (Minuchin, 1974) and found that cohesive, balanced, and secure family types tend to form the majority (Lindblom et al, 2014; Johnson, 2010). The phenomenon of highly secure families in conditions of severe unsafety may indicate parents’ commitment and motivation to protect their children’s development and well-being in war zones.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both the children and parents in these families reported high attachment security, and the children also exhibited low avoidance. The results concur with research empirically confirming the emergence of the classic family systems (Minuchin, 1974) and found that cohesive, balanced, and secure family types tend to form the majority (Lindblom et al, 2014; Johnson, 2010). The phenomenon of highly secure families in conditions of severe unsafety may indicate parents’ commitment and motivation to protect their children’s development and well-being in war zones.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to research on family systems in peaceful societies (Johnson, 2010; Lindblom et al, 2014), the study revealed multiple family dynamics. Among Palestinians, a secure family type with warm siblingship and optimal parenting practices was more than twice as common as an insecure family type with very negative relational patterns (36% vs 16%).…”
Section: Discussionmentioning
confidence: 60%
“…We acknowledge the differences in sample size across classes and the possibility of increased probability of Type I errors of these post-hoc comparisons; all remaining classes, however, constituted greater than 5% of the sample, in line with Lindblom et al’s (2014) decision to retain classes larger than 4%. In the ANOVA testing, we used Tukey post-hoc tests to reduce risk of Type I error due to multiple testing when comparing means across classes.…”
Section: Resultsmentioning
confidence: 95%
“…A recent study by Lindblom and colleagues (2014) highlights the complexity of group-based analyses when multiple dimensions over multiple timepoints for multiple individuals were examined. The resulting groups were much smaller in size than those identified when analyzing a single dimension for one individual separately.…”
Section: Positive and Negative Relationship Dimensionsmentioning
confidence: 99%
“…By law, both parents can take parental leave, and many fathers take advantage of this opportunity. However, despite a relatively high level of equality in parenting roles, previous studies have shown some gender differences between parents’ experiences and expectations of parenting and family relationships also in Finland (Lindblom et al, ; Flykt et al, ).…”
mentioning
confidence: 96%